ҚАРАҚАЛПАҚЛАРДЫҢ ТАРИЙХЫЙ МӘКАН ҲӘМ ЗАМАНДА ПАЙДА БОЛЫЎЫ ҲӘМ ҚӘЛИПЛЕСИЎИ - Усенов, Ж.; Дабылов, А. (FAN va JAMIYAT, 2021)
This article reflects the formation of the Karakalpak people in a particular historical region and the fact that this people has a comprehensive position in the series of periods. It was also noted that the Karakalpak people are distinguished among the fraternal peoples by their rich national culture and national mentality. This article also provides an objective and detailed assessment of the history of a nation with a great past and an even greater future. In particular, this article discusses the ethnic history and ethnogenesis of the ancient statehood traditions of the Karakalpak people.